Optoelectronic oscillator at s-band and c-band for 5g telecommunications purpose (2020)
This article presents the implementation results for two optoelectronic oscillators at 2.2 GHz and 5.7 GHz; and the proof-of-concept of the integration of photonics components into a microwave communication link. The oscillators are characterized for frequency stability. The phase noise values achieved are −101.1 dBc/Hz at 10 kHz offset for the 2.2 GHz optoelectronic oscillator and −100.3 dBc/Hz at 10 kHz offset for the 5.7 GHz optoelectronic oscillator. The implemented microwave link is evaluated using the Error Vector Magnitude (EVM) for a 2.2 GHz transmission with a 4 symbols QPSK modulation.